A Review on Smart Surface-Engineered Nanoparticles for Precision Drug Delivery: Review article (Journal of Pharma Insights and Research, 2026)
Precision medicine relies on the development of therapeutic systems capable of molecular-level manipulation. Traditional drug delivery remains restricted by poor bioavailability, rapid systemic clearance, and non-specific distribution, leading to adverse effects in healthy tissues. Surface-engineered nanocarriers address these hurdles through sophisticated functionalization strategies. Organic, inorganic, and carbon-based nanoplatforms provide versatile templates for encapsulation and controlled release. Functional layers, such as polyethylene glycol, establish a hydrated shield that prevents opsonization and extends circulation half-life. Integration of specific ligands including antibodies, peptides, and small molecules enables active targeting through receptor-mediated endocytosis, facilitating site-specific accumulation at diseased sites like solid tumors. Stimuli-responsive designs allow for triggered release in response to pathological environments, such as acidic pH or enzymatic overexpression. Specialized techniques like red blood cell hitchhiking and the recruitment of endogenous proteins allow for the traversal of the blood-brain barrier and pulmonary endothelium. Despite therapeutic potential, clinical translation is delayed by manufacturing complexities, batch-to-batch variability, and immunological responses such as accelerated blood clearance. Refining the nano-bio interface through biomimetic design remains essential for achieving consistent human clinical efficacy. Successful implementation of these smart platforms marks a significant shift toward personalized, patient-centric therapeutics, offering a clear path to minimize systemic toxicity while maximizing curative outcomes across various diseases